Development of a temperature-controlled solar powered ventilation system - Nuraini, Abdullah; Nurulain, S.; Mohd Amir Shahlan, Mohd Aspar; Mohd Rashidi, Salim; Hadi, Manap (EDP Sciences, 2024)
Wind-driven ventilators like roof whirlybirds rely purely on wind and thermal expansion to operate. Consequently, they fail to function effectively in the absence of wind. Moreover, they only commence ventilating when heat accumulates in the roof space, indicating an underlying issue of the roof becoming excessively warm. Consequently, an alternative ventilation system that can effectively address the heat problem is essential. In this regard, a solar-powered ventilation system is reported as a viable solution. This developed system operates based on the temperature conditions of the ceiling, where the fan speeds up during hot weather and slows down or stops once a certain cool temperature is reached. This temperature-controlled characteristic distinguishes it from other solar-powered ventilation systems that operate at a constant speed. Through continued research and improvement, it is expected that this new temperature-controlled ventilation system has good potential to be commercialized.